Face Observance in Twitter Conversations - Moch. Armie Syifaa Sutaro (Passage, 2015)
This research entitled Face Observance in Twitter Conversationsis aimed at investigating the politeness strategies used by the speakers in observing and non-observing their hearers’ face in Twitter conversations, the response given by the hearers, and the effects which may be resulted from (non) observance. This study employs a descriptive qualitative study. The data were taken from conversations made in Twitter.This study showed that the four types of politeness strategies proposed by Brown and Levinson (1987) namely, bald-on-record, positive politeness, negative politeness, and off-record are used by the speakers in observing and non-observing their hearers’ negative and positive face. The hearers’ response to the (non) observance done by the speakers by using different strategies may produce some effects to the conversation itself. The result shows that there are two kinds of effects resulted from (non) observance done by the speakers. The first effect is that the conversation goes well without any distraction while the second one is that the conversation is distracted or even stopped. It is suggested that positive politeness strategy seems to be the preferred choice taken by the participants in maintaining a conversation.Keywords: Face, Observance,Politeness, Face Threatening Acts, Politeness StrategiesKeywords: Face, Observance,Politeness, Face Threatening Acts, Politeness Strategies